Estudio de la interferencia de pozos en la administración Farias de la Empresa Agroindustrial Casa Grande S.A.A. - Ruiz Rodriguez, Ronald Ivan (2008)
In this paper we study the operation of a field of wells (drums), which draws water from an aquifer free, working steady. The method of calculating equations are proposed hydro wells. There is a system of linear equations, which provides drops in each well. By application of the method to the case of a battery of 32 wells located in the Administration Farias of the Casa Grande Agroindustrial Company SAA, in which soon will be drilling tube wells for the extraction of groundwater. They are necessary definitions on terms attached to this work, and which is presented in the introductory part. We need to work as field measurement of levels, aforos, pumping tests and sondajes electric. We found the hydraulic parameters, which we assume with sorne values for the entire area, but for more accuracy was flat INRENA to confirm and support their values. We determined whether there was interference between wells on drums and find rays of influence for each respective pit, which we find that in most cases there is interference, in sorne areas more than others. Finally, an analysis of lost productivity due to interference, which shows that these losses compared with profits ·of the entire area of the company, are tiny and not be given due concern in seeking an ideal balance in a matter of efficiency Well and economy